Peran Lembaga Keuangan Mikro (LKM) Dalam Upaya Pengembangan Usaha Kecil Dan Mikro - Passa Sayyid Akbar Lubis; Imsar Imsar (Trending: Jurnal Manajemen dan Ekonomi, 2024)
Small and medium enterprises in strong growth companies in crisis conditions. It is between the lines to the east that changes in relative income vary between tadana and also because money depends on local production factors. Yesterday I wrote a story, because I often think there are many obstacles, one of which is short or small capital. They are unprofessional and subordinate to increasingly petty interests. This building is classified as non-residential (not permanent). MFIs operate many micro and small businesses. It has a more convenient microwave that can be used for smaller and smaller businesses. This book is designed to 1) improve the performance of MFIs in small and medium businesses, 2) increase the prospects and development of MFIs. LKM also offers a wide range of microbiological and microbial conservation pets. LKM must be a regular member with time consuming micro and micro device reading for formatted access. MFI has a bike option has more cars and microns, has a narrow car but not many models. Rebuilding LKM as a business requires rebuilding LKM as a commercial enterprise that is generated by implementing maintenance and operational strategies that increase cottage payments on credit. One obstacle to the agricultural efforts of Borasal MFIs lies in: rural areas and their agricultural fields. interior: functional and human elements sum-est